CONSEQUENCES OF DELAYING DISTRIBUTION OF ESTATE IN ISLAMIC LAW OF INHERITANCE: THE NIGERIAN EXPERIENCE - Saka Ismael, Ismael (Jurnal Syariah, 2017)
This paper investigates the consequences of delaying distribution of an estate of a deceased Muslim using a particular area of Nigeria (Ilorin, Kwara State) as a case study. The results show that inordinately delaying the sharing of the estate of a deceased Muslim has grave consequences which manifests socially, economically, religiously, and legally. This is illustrated through a number of decided and ongoing cases from the areas under reference. This study is therefore meant to serve as a standard by which Muslims may apply Shariah rulings regarding estate holdings in their respective communities. However, applications of the law may vary slightly depending on the particular madhab chosen.